Engaging Researchers with Data Management : The Cookbook (2021)
Research data management is no longer a new or unknown concept for today’s researchers, but nonetheless it can be intimidating. Many universities, institutes, organisations, and funding agencies have guidelines, mandates, and even policies around data management. But that does not make the task any less daunting; indeed it often adds a complicated layer of work and effort to data-producing research activities. Domain- and discipline- specific data comes in all sizes and forms, so specialised information is required to facilitate correct research data management. In addition, in recent years the very important and highly popular ‘FAIR’ principles1 have been brought into the picture.